IRISH REPUBLICAN COUNTERPUBLIC ([S.l.])
1 online resource
Keywords: This volume examines the critical factors and processes by which the Provisional Irish Republican movement campaign from 1969 to 1998 transformed a once acquiescent nationalist population in Northern Ireland into a counterpublic of resistance demanding national self-determination and social justice. Considering the establishment of Irish Republican community institutions, prison protests, Republican Feminism, and Provisional IRA media and communications, this volume explores the emergence of Republicanism as a mass social movement in the nationalist Catholic ghettos and rural regions of Northern Ireland in the 1970s - a development that helped to sustain the armed struggle of the Provisional Irish Republican Army for three decades. An examination of the emergence and transformative power of the counterpublic discourse and action of the Irish Republican movement, this volume provides a framework for conceptualizing counterpublics in social movement studies. As such it will appeal to scholars of sociology, history, and politics with interests in social movements and mobilization.